Empowering student-led initiatives: integrating social action into higher education curriculum in West Java - Erli Sarilita; Nani Murniati; Harmas Yazid Yusuf (Perspectives in Education, 2025)
This article presents a comprehensive examination of a pioneering social action endeavor led by first-year bachelor and vocational students in Sumedang, West Java. Integrating principles of science literacy, environmental stewardship, and community health promotion, the initiative comprised three distinct components: science literacy engagement for pupils, waste cleaning activities, and a healthy food campaign at elementary school canteens. Drawing upon participatory methodologies, the article reported the planning, implementation, and outcomes of these interconnected initiatives, shedding light on the transformative potential of student-led initiatives in addressing pressing societal challenges. The article highlights the multifaceted impact of these interventions on both the participating students and the broader community. The findings underscore the importance of fostering civic engagement and social responsibility within educational curricula, emphasizing the role of students as catalysts for positive change in their communities.